The molecular mechanism underlying unconventional secretion of Fibroblast Growth Factor 2 from tumour cells - Steringer, Julia P.; Nickel, Walter (Biology of the cell, 2017)
Abstract Fibroblast Growth Factor 2 (FGF2) is a potent cell survival factor involved in tumour?induced angiogenesis. FGF2 is secreted from cells through an unconventional secretory mechanism based upon direct translocation across the plasma membrane. The molecular mechanism underlying this process depends on a surprisingly small set of trans?acting factors that are physically associated with the plasma membrane. FGF2 membrane translocation is mediated by the ability of FGF2 to oligomerise and to insert into the plasma membrane in a PI(4,5)P2?dependent manner. Membrane?inserted FGF2 oligomers are dynamic translocation intermediates that are disassembled at the extracellular leaflet mediated by membrane proximal heparan sulphate proteoglycans. This process results in the exposure of FGF2 on cell surfaces as part of its unconventional mechanism of secretion. Although the trans?acting factors and cis?elements in FGF2 required for unconventional secretion have been known for a while, the core mechanism of this mysterious process has now been reconstituted with purified components establishing the molecular basis of FGF2 secretion from tumour cells.